2007
DOI: 10.1007/s00264-007-0356-3
|View full text |Cite
|
Sign up to set email alerts
|

Intramedullary tibial nailing in distal third tibial fractures: distal locking screws and fracture non-union

Abstract: Distal third tibial fractures are prone to non-union following tibial nail insertion. The purpose of this study was to assess the union of distal third tibial fractures in patients who have undergone intra-medullary (IM) tibial nailing with one versus two distal locking screws. Sixty-five patients who had intramedullary tibial nail fixation were retrospectively analysed. Our results showed that 80% of non-unions in distal third fractures had only one distal locking screw compared to 20% who had two distal lock… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
30
0
4

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(41 citation statements)
references
References 15 publications
7
30
0
4
Order By: Relevance
“…Mohammed et al studied relation of nonunion and distal interlocking and showed that there was a high incidence of non-union in distal third tibia fractures treated with IM nailing when only one distal locking screw was used. 6 Therefore, they recommend two distal locking screws in IM nail fixation of distal third tibia fractures. If two distal locking screw insertions are not possible due to the distal nature of the fracture, they recommend an alternate form of fixation.…”
Section: Discussionmentioning
confidence: 99%
“…Mohammed et al studied relation of nonunion and distal interlocking and showed that there was a high incidence of non-union in distal third tibia fractures treated with IM nailing when only one distal locking screw was used. 6 Therefore, they recommend two distal locking screws in IM nail fixation of distal third tibia fractures. If two distal locking screw insertions are not possible due to the distal nature of the fracture, they recommend an alternate form of fixation.…”
Section: Discussionmentioning
confidence: 99%
“…With upcoming implant technology, indication for intramedullary tibial nailing has extended towards extraarticular fractures of the distal third of the bone [5,6]. This change is accompanied by adverse effects like high rates of delayed bone healing, nonunion or malalignment and an incidence of distal locking screw failure ranging from 6 % to 14 % [1,3,7,8].…”
Section: Introductionmentioning
confidence: 99%
“…There is one area of agreement among trauma surgeons: these fractures need to be treated operatively [1][2][3][4]. The standard treatment option includes open reduction and internal fixation using angular stable plate osteosynthesis.…”
Section: Introductionmentioning
confidence: 99%